Assessing the Efficacy of Parental Testosterone Therapy in the Penis Size Before Hypospadias Surgery - Praveen S. Baghel; Anil Dawar; Roshan Mandloi; Sarika Rawat; Sonu Rawat (Journal of Pharmacy and Bioallied Sciences)
Background: Parenteral testosterone has been used to increase glans diameter and penis size before hypospadias surgery. However, the existing literature data are scarce in the Indian context. Aim: The present study aimed to assess the efficacy of parenteral testosterone injection on diameter at the base of the penis, glans diameter, and penile length before surgery. Methods: The study assessed 40 hypospadia subjects who were given testosterone propionate injection a 2 mg/kg body weight dose given deep intramuscularly in three doses at 3-week gap before reconstructive surgery. Before surgery, diameter at the base of the penis, glans diameter, and penile length was assessed. Results: The study results showed a mean increase in diameter at the base of the penis, glans diameter, and penile length after parenteral testosterone therapy as 0.94 ± 0.14, 1.03 ± 0.48, and 1.09 ± 0.25, respectively. All three factors were statistically significant with P < 0.001. Conclusion: Intramuscular testosterone injection leads to an increase in diameter at the base of the penis, glans diameter, and penile length without any notable associated severe side effects. However, minor side effects are associated, including aggressiveness, acne, and fine pubic hair development.